Large mammal diets and paleoecology across the Oldowan–Acheulean transition at Olduvai Gorge, Tanzania from stable isotope and tooth wear analyses. Issue 120 (July 2018) - Uno, Kevin T.; Rivals, Florent; Bibi, Faysal; Pante, Michael; Njau, Jackson; de la Torre, Ignacio
Abstract: The well-dated Pleistocene sediments at Olduvai Gorge have yielded a rich record of hominin fossils, stone tools, and vertebrate faunal remains that, taken together, provide insight to hominin behavior and paleoecology. Since 2008, the Olduvai Geochronology and Archaeology Project (OGAP) has undertaken extensive excavations in Bed II that have yielded a large collection of early Pleistocene stone tools and fossils. The strata of Lower, Middle and Upper Bed II at Olduvai Gorge capture the critical transition from Oldowan to Acheulean technology and therefore provide an opportunity to explore the possible role of biotic and abiotic change during the transition. Here, we analyze newly discovered and existing fossil teeth from Bed II sites using stable isotope and tooth wear methods to investigate the diets of large mammals. We reconstruct the dietary ecology of Bed II mammals and evaluate whether vegetation or hydroclimate shifts are associated with the technological change. Combined isotope and tooth wear data suggest most mammals were C4 grazers or mixed feeders. Carbon isotope data from bulk enamel samples indicate that a large majority of Bed II large mammals analyzed had diets comprising mostly C4 vegetation (>75% of diet), whereas only a small number of individuals had either mixed C3 –C4 or mostly C3 diets (<25% C4 ). Mesowear generally indicates an increase of the abrasiveness of the diet between intervals IIA and IIB (∼1.66 Ma), probably reflecting increased grazing. Microwear indicates more abrasive diets in interval IIA suggesting stronger seasonal differences at the time of death during this interval. This is also supported by the intratooth isotope profiles from Equus oldowayensis molars, which suggest a possible decrease in seasonality across the transition. Neither stable isotope nor tooth wear analyses indicate major vegetation or hydrological change across the Oldowan–Acheulean transition.